Mediating the margins: the role of brokers and the Eastern Provincial Council in Sri Lanka's post-war transition. Issue 6 (1st November 2016) - Goodhand, Jonathan; Klem, Bart; Walton, Oliver
Abstract: This article explores the political dynamics surrounding the Eastern Provincial Council during Sri Lanka's post-war transition. We show that decentralisation constituted an intervention in conflict, rather than a solution to it. It creates new institutional arenas to re-negotiate centre-periphery relations, resulting in new forms of political mobilisation. There are crucial spatial dimensions to these contentions: it involves contested territorialisation of power, scalar manoeuvring, and boundary drawing. These are explored in Sri Lanka's Eastern Province, with particular reference to the role performed by brokers in mediating centre-periphery relations, through and alongside the Provincial Council.